Output growth differentials across the euro area countries - some stylised facts - Nicholai Benalal; Juan Luis Diaz del Hoyo; Beatrice Pierluigi; Nikiforos Vidalis (European Central Bank (ECB), 2006)
The aim of this study is to investigate the extent to which the dispersion of real GDP growth rates has changed over the past few years and whether the synchronisation of business cycles has increased among the euro area countries. The study is divided into two main parts. The f irst focuses on the dispersion of real GDP growth rates across the euro area countries, while the second studies the synchronisation of business cycles within the euro area. The study shows first that dispersion of real GDP growth rates across the euro area countries in both unweighted and weighted terms has no apparent upward or downward trend during the period 1970-2004 as a whole. Second, since the beginning of the 1990s, the dispersion of real GDP growth rates across the euro area countries has largely reflected lasting trend growth differences, and less so cyclical differences, with some countries persistently exhibiting output growth either above or below the euro area average. Among other things, this might be due to different trends in demographics, as well as to differences in structural reforms undertaken in the past. Thirdly, the degree of synchronisation of business cycles across the euro area countries seems to have increased since the beginning of the 1990s. This f inding holds for various measures of synchronisation applied to overall activity and to the cyclical component, for annual and quarterly data, as well as for various country groupings. In particular, the degree of correlation currently appears to be at a historical high. In addition to these main findings, certain other stylised facts on dispersion and synchronisation are presented.
Keywords: C10; E32; O40; 330; Dispersion of GDP growth across the euro area countries; trend and cycle; synchronisation of business cycles within the euro area.; Wirtschaftswachstum; Konjunkturzusammenhang; Eurozone; EU-Staaten